Pelatihan Mendeley Bagi Guru SMP N 1 Muaro Jambi untuk Meningkatkan Keterampilan Menulis Karya Ilmiah - Yusuf, Muhammad; Sadikin, Ali; Sembiring, Dian Arisandy Eka Putra; Mursyd, Danial; Mardiyanti, Lely (Jurnal JUPEMA, 2025)
This community service activity aims to improve the scientific writing skills of teachers at SMP N 1 Muaro Jambi. Basically, Mendeley is used as a reference management tool, especially in creating scientific papers. However, many teachers face obstacles in managing reference sources systematically and efficiently. This training is designed to provide an understanding of the main functions and features of Mendeley. The training was conducted offline using presentation, discussion and practice methods. The training participants consisted of 25 teachers at SMP N 1 Muaro Jambi. Based on the test results, after participating in the training, on average, teachers showed an increase in their ability to manage references from the original 45% to 85%. Of course, these results provide a positive indication for producing scientific works with sufficient and valid references.   Keywords: Mendeley, writing skills, scientific papers, teachers